2011
DOI: 10.1093/eurpub/ckr188
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus awareness, knowledge and vaccine acceptance: A survey among 18-25 year old male and female vocational school students in Berlin, Germany

Abstract: Results indicate a need for better education about HPV that should extend beyond its link with cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
104
9
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(147 citation statements)
references
References 33 publications
21
104
9
13
Order By: Relevance
“…Direct comparison of the results of this survey with data of similar published results is complicated by the fact that the methodology vary between studies in terms of characteristics of each population, data collection, and ways of reporting. The level of knowledge is higher than those obtained in 18 to 25-year-old students in Germany which only 13.9% knew that HPV infection is sexually transmitted and <15% knew that HPV infects women and men, 33 in a group aged 18-24 in Singapore only 15.2% had ever heard of HPV, 31 in males aged 12-22 y in India respectively 31.5% and 28% were aware that HPV infection causes genital cancer and of availability of vaccine, 35 in the United Arab Emirates 31% of university students had not heard of HPV infection before, 34 in Hungary among adolescents 12 and 19 y only 35% have heard of the HPV and 46.6% knew that HPV infection may be transmitted by vaginal intercourse, 32 and in the US respectively 38.3% and 33.1% of respondents had heard of HPV and of the vaccine. 16 Not surprising only 4 students in this study have been vaccinated against HPV, but one important observation was that almost 2-thirds were likely to be vaccinated against HPV.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Direct comparison of the results of this survey with data of similar published results is complicated by the fact that the methodology vary between studies in terms of characteristics of each population, data collection, and ways of reporting. The level of knowledge is higher than those obtained in 18 to 25-year-old students in Germany which only 13.9% knew that HPV infection is sexually transmitted and <15% knew that HPV infects women and men, 33 in a group aged 18-24 in Singapore only 15.2% had ever heard of HPV, 31 in males aged 12-22 y in India respectively 31.5% and 28% were aware that HPV infection causes genital cancer and of availability of vaccine, 35 in the United Arab Emirates 31% of university students had not heard of HPV infection before, 34 in Hungary among adolescents 12 and 19 y only 35% have heard of the HPV and 46.6% knew that HPV infection may be transmitted by vaginal intercourse, 32 and in the US respectively 38.3% and 33.1% of respondents had heard of HPV and of the vaccine. 16 Not surprising only 4 students in this study have been vaccinated against HPV, but one important observation was that almost 2-thirds were likely to be vaccinated against HPV.…”
Section: Discussioncontrasting
confidence: 59%
“…[29][30][31] Unfortunately all these issues among young males have only been studied to a limited extent. [32][33][34][35][36] Specifically in Italy, few studies have been conducted among different groups, [37][38][39] but to the authors' knowledge little is known to date regarding HPV vaccination in young males. It remains imperative this evaluation in order to identify information needs and to design future strategies for expanding cancer prevention.…”
Section: Introductionmentioning
confidence: 99%
“…6 Previously conducted coverage studies from Germany, which were mainly based on survey data, have shown heterogeneous results, depending on the considered age group, region, and study population. [3][4][5]7 Direct comparability of our results with those studies is hampered by different aspects. First of all, an estimation of the vaccination coverage rather than the vaccine uptake was not possible in the context of the present study due to the limited study period (only the year 2008), for which the data was available.…”
mentioning
confidence: 87%
“…2 Based on data from several surveys, HPV vaccination coverage in Germany with at least one vaccine dose ranged from 12% in females aged 12-20 y to 67% in females aged 18-20 y. [3][4][5] In one of these studies, the proportion of girls not knowing, whether they had received the vaccination was shown to be 57%, 5 suggesting that recall bias might considerably affect the validity of self-reported data in this context. 6 Vaccination record review (n = 161) including females aged 14-19 y showed an HPV vaccination coverage with all three recommended doses of 41% in the federal state of Berlin.…”
mentioning
confidence: 99%
See 1 more Smart Citation